2016
DOI: 10.1038/ncomms10654
|View full text |Cite
|
Sign up to set email alerts
|

GAME9 regulates the biosynthesis of steroidal alkaloids and upstream isoprenoids in the plant mevalonate pathway

Abstract: Steroidal glycoalkaloids (SGAs) are cholesterol-derived molecules produced by solanaceous species. They contribute to pathogen defence but are toxic to humans and considered as anti-nutritional compounds. Here we show that GLYCOALKALOID METABOLISM 9 (GAME9), an APETALA2/Ethylene Response Factor, related to regulators of alkaloid production in tobacco and Catharanthus roseus, controls SGA biosynthesis. GAME9 knockdown and overexpression in tomato and potato alters expression of SGAs and upstream mevalonate path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
286
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 271 publications
(299 citation statements)
references
References 63 publications
13
286
0
Order By: Relevance
“…In a recent example, Cárdenas et al (2016) demonstrated that an AP2-type transcription factor (GLYCOALKALOID METABOLISM9 [GAME9]) could likely activate genes of the clustered steroidal glycoalkaloid pathway genes such as GAME4. Yet, GAME9 is located on chromosome 1 and hence is not physically associated with the steroidal glycoalkaloid cluster genes situated on chromosomes 7 and 12 in tomato and potato (Solanum tuberosum).…”
Section: Common and Unique Features Of The B-diketone Metabolic Genementioning
confidence: 99%
“…In a recent example, Cárdenas et al (2016) demonstrated that an AP2-type transcription factor (GLYCOALKALOID METABOLISM9 [GAME9]) could likely activate genes of the clustered steroidal glycoalkaloid pathway genes such as GAME4. Yet, GAME9 is located on chromosome 1 and hence is not physically associated with the steroidal glycoalkaloid cluster genes situated on chromosomes 7 and 12 in tomato and potato (Solanum tuberosum).…”
Section: Common and Unique Features Of The B-diketone Metabolic Genementioning
confidence: 99%
“…Op ERF2 was assigned to the clade that is composed of group IX ERFs, with the members previously reported to be involved in specialized metabolism. Interestingly, Op ERF2 exhibited a closer relationship with C. roseus ORCA2 and ORCA3 that regulate MIA biosynthesis than with Sl JRE4, Nb ERF1, Nt ERF189, and Nt ORC1, the ERFs from Solanaceae family that regulate SGA and nicotine alkaloids biosynthesis (van der Fits and Memelink, 2000, 2001; Shoji et al, 2010; Todd et al, 2010; Cárdenas et al, 2016; Thagun et al, 2016) or Aa ERF1 and Aa ERF2 from Asteraceae family that regulate terpenoid biosynthesis (Yu et al, 2012). Op ERF4 and Op ERF5 were classified into a separated cluster that exclusively consists of Arabidopsis group IXc ERFs.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, Cr ORCA2 and Cr ORCA3 are classified as APETHALA2/Ethylene Response Factor (AP2/ERF). AP2/ERF represents a superfamily of transcription factor that plays an important role in plant biological systems, such as growth and development (Chuck et al, 1998; Ohto et al, 2009), response to stimuli (Licausi et al, 2010; Mizoi et al, 2012; Zhao et al, 2012), and biosynthesis of primary and secondary metabolites (van der Fits and Memelink, 2000, 2001; Zhang et al, 2005; Shoji et al, 2010; Todd et al, 2010; Cárdenas et al, 2016; Thagun et al, 2016). On the basis of the number of conserved AP2/ERF domain and the existence of a family-specific B3 domain, AP2/ERFs are further classified into three families: AP2, ERF, and RAV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, unlike other plants, Solanaceae plant species also accumulate cholesterol as a major sterol [56, 57]. The biosynthesis of cholesterol in Solanaceae has not been elucidated yet, but was shown to involve a sterol side chain reductase enzyme (SSR) 2 that catalyzes the conversion of cycloartenol into cycloartanol by reduction of the C-24(25) double bond.…”
Section: Resultsmentioning
confidence: 99%